The MESSy DWARF (based on MESSy v2.55.2) - A. Kerkweg; A. Kerkweg; T. Kirfel; T. Kirfel; D. H. Do; S. Griessbach; S. Griessbach; P. Jöckel; D. Taraborrelli; D. Taraborrelli (Geoscientific Model Development)
The adaptation of Earth system model (ESM) codes to modern computing architectures is challenging as ESMs consist of a multitude of different components. Historically grown and developed by scientists rather than software engineers, the codes of the individual components are often interwoven, making the optimisation of the ESMs rather challenging, if not impossible. Thus, in the last few years, the codes have become increasingly modularised, and, with that, different components are now disentangled from each other. This helps porting the code section by section to modern computing architectures, e.g. to GPUs.